Checklist, key and latitudinal distribution of the eastern Atlantic marine gobies along the European coast (Actinopterygii: Gobiidae and Oxudercidae) - Kovačić, Marcelo; Svensen, Rudolf; Renoult, Julien P.; Patzner, Robert A. (Zootaxa, 2025)
The checklist of 34 marine gobiid species (Actinopterii: Gobiidae and Oxudercidae) with confirmed records is compiled for the Atlantic coast of Europe, including four alien gobiid species found in transitional waters or in the low salinity waters of the Baltic Sea. An identification key for the gobiid species known from the area is also provided. The latitudinal distribution of native goby species in this area is presented and discussed. Finally, the second northernmost record of a Gobiidae fish is reported, corresponding to Pomatoschistus minutus (Pallas, 1770) from Tromsø, Norway.